Implementasi Pergerakan Lengan Robot Dengan Flex-Sensor Menggunakan Kalman Filter - Hanif Yudha Prayoga; Rizal Maulana; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The advancement in the world of technology today is very rapidly, especially in the robotics. Creation of robots is based on processes to assist human activities, ranging from easy to heavy and dangerous jobs. With a manipulator robot (robotic arm) a company has the advantage to save more worker and reduce human mistakes. Robot Manipulator is a mechanical part that can be enabled to move, lift and manipulate an object. The robotic arm consists of actuators and some DOF (Degree of Freedom) which is useful as a tool of motion of the robotic arm. To move the robot itself required some sensor, and flex sensor is a sensor to identify the resistance of human arm movement. But to move the robotic arm required a method for the output of the arm has a good accuracy then Kalman filter is used that serves to reduce the value of uncertainty caused noise in the sensor readings. In this study, a robot arm was made using Arduino UNO and servo motors as robotic arm output. The use of Arduino UNO because it has facilities DC jack that can be used for sensors. As well as the servo motor, the servo motor can set the value of the degrees of movement. From the results, the robotic arm can perform movement according to input from the human arm. The robot can move and can perform some combination of movement using Kalman filter method with 100% success rate.